2014
DOI: 10.1016/j.jcpa.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factors and Receptors in Canine Lymphoma

Abstract: Platelet-derived growth factors (PDGFs) belong to a family of polypeptide growth factors that signal through cell surface tyrosine kinase receptors to stimulate growth, proliferation and differentiation. Platelet-derived growth factor receptors (PDGFRs) are also considered important targets for specific kinase inhibitors in the treatment of several human tumours. The aim of this study was to investigate the role of PDGF-A, PDGF-B, PDGFR-α and PDGFR-β in canine lymphoma by determining gene and protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In domestic animal tumours, the IHC expression of PDGFRs has been investigated in astrocytoma, lymphoma, osteosarcoma, anal sac adenocarcinoma, thyroid carcinoma and haemangiosarcoma, highlighting the importance of these receptors also in the tumour biology of animals, as it occurs in humans . However, for none of these tumours a prognostic relevance has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…In domestic animal tumours, the IHC expression of PDGFRs has been investigated in astrocytoma, lymphoma, osteosarcoma, anal sac adenocarcinoma, thyroid carcinoma and haemangiosarcoma, highlighting the importance of these receptors also in the tumour biology of animals, as it occurs in humans . However, for none of these tumours a prognostic relevance has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this resistance is facilitated by the activation of P-glycoprotein (P-gp), other drug transporters, or a combination of both [ 18 ]. Angiogenesis is required for the survival of hematologic cancers [ 20 ] and the expression patterns of angiogenic growth factors, including platelet-derived growth factor receptor (PDGFR) and vascular endothelial growth factor receptor (VEGFR), correlate with clinical stage and historical grade in canine lymphoma [ 2 , 15 ]. Additionally, overexpression of PDGFR and VEGFR promotes resistance to several anti-cancer drugs [ 1 , 14 ].…”
mentioning
confidence: 99%
“…Several research groups have reported that elevated HIF-1α levels have been linked to poor prognoses in human diffuse large-B-cell lymphoma [20, 21]. Other groups suggested that the expression patterns of PDGF, VEGF and survivin in canine lymphoma correlate with clinical stage and histological grade [19, 22, 23]. Hypoxic stimulation effectively may improve growth potential and invasiveness of canine lymphoma cells in response to upregulation of PDGF , VEGF and survivin expression.…”
Section: Discussionmentioning
confidence: 99%